Facile preparation of cellulose fiber reinforced polypropylene using hybrid filler method - Mustapha, Safarul; Lease, Jacqueline; Eksiler, Kubra; Sim, Siew Teng; Ariffin, Hidayah; Andou, Yoshito (Multidisciplinary Digital Publishing Institute, 2022)
Dried hybrid fillers comprised of silica/CNF were successfully synthesized in ethanol/water mixed solvents at room temperature without the usage of any precursor. The as-prepared fillers were incorporated with polypropylene (PP) as a polymer matrix through a twin-screw extruder. From surface morphology analysis, the agglomeration of the silica/CNF hybrid fillers was prevented in the PP matrix and they exhibited moderate transparency, around 17.9% and 44.6% T at 660 nm. Further, the chemical structures of the polymer composites were identified by Fourier transform infrared (FT-IR) analysis. According to thermogravimetric analysis (TGA), the insertion of silica as a co-filler to the PP matrix resulted in an increase in its degradation onset temperature and also thermal stability. In addition, the mechanical properties of the PP composites also increased after the blending process with the hybrid fillers. Overall, sample PP-SS/CNF exhibited the highest tensile strength, which was 36.8 MPa, or around 73.55% compared to the pristine PP. The improvements in tensile strength were attributed to good dispersion and enhanced efficiency of the stress transfer mechanism between the silica and the cellulose within the PP matrix. However, elongation of the sample was reduced sharply due to the stiffening effect of the filler.